2019
DOI: 10.3390/pr7110836
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Dynamics of Carbon Storage in Response to Urbanization: A Case Study in the Su-Xi-Chang Region, China

Abstract: Terrestrial ecosystem carbon storage plays an important role in mitigating global warming. Understanding the characteristics and drivers of changes in carbon storage can provide a scientific basis for urban planning and management. The objective of this study was to reveal the ways in which urbanization influences the spatial and temporal variations in carbon storage. In this study, we investigated the changes in carbon storage from 1990–2000, 2000–2010, and 2010–2018 in the Su-Xi-Chang region, which is a typi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…Since the carbon density data were collected from the results of studies in different parts of China, the selected documents should be close to or similar to the study area as far as possible to avoid excessive data gap. At the same time, the carbon density varies with climate, soil properties and land use 38 , so the carbon density should be modified according to the climate characteristics and land use types of the Western Sichuan Plateau. Existing research results show that the carbon density is positively correlated with annual precipitation and weakly correlated with annual average temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Since the carbon density data were collected from the results of studies in different parts of China, the selected documents should be close to or similar to the study area as far as possible to avoid excessive data gap. At the same time, the carbon density varies with climate, soil properties and land use 38 , so the carbon density should be modified according to the climate characteristics and land use types of the Western Sichuan Plateau. Existing research results show that the carbon density is positively correlated with annual precipitation and weakly correlated with annual average temperature.…”
Section: Methodsmentioning
confidence: 99%
“…However, a minority of scholars have begun to focus on the impacts of urbanization on critical ESs that maintain regional ecological security. It was found that rapid urban expansion in China often triggers changes in the regional natural environment [23], causing a series of ecological problems such as regional soil erosion, low-lying water bodies, reduced carbon storage, soil erosion and loss of biodiversity, weakening ESs and threatening regional sustainable development [24][25][26], with biodiversity conservation, outdoor recreation, water production, carbon storage, heat island mitigation ESs such as biodiversity conservation, outdoor recreation, water production, carbon storage, heat island mitigation and soil erosion are the most sensitive to urbanization [27][28][29][30]. Overall, previous studies have focused more on the impact of urbanization on which ESs that maintain regional ecological security, but there is still a lack of research on the spatial heterogeneity of the impact of urbanization on critical ESs to guide the synergistic development of regional urbanization development and ecosystem conservation [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…The Su-Xi-Chang region is a typical representation of a developed economic agglomeration. Rapid advances in industrialization and urbanization cause severe changes in land use coverage [28][29][30][31][32]. Hence, exploring the spatio-temporal pattern of land use conflicts in the Su-Xi-Chang region provides scientific guidance for the implementation of "three space and three Lines" in urban agglomerations and points out to new ideas for resolving the contradiction between culture and nature.…”
Section: Introductionmentioning
confidence: 99%